Orientaciones profesionales de los comunicadores sociales - Rivadeneira Lara, Emmily Nathalie (2017)
The following research paper exposes the present situation of social communicators in the city of Guayaquil, in the political, social, labor and academic field. It emphasizes the professional profile that each communicator possesses in the different professional fields in which he is currently immersed due to the transformations of the labor market, changes that have allowed the communicator to adapt professionally in areas conceived thanks to the technological evolution of the new century, placing Research to the knowledge of the various branches of communication, such as Digital Journalism, Community Management, Public Relations, Organizational Communication and Journalism through traditional media. Professional areas that are represented as occupational alternatives in the labor market of a social communicator today.